Ivermectin-induced changes in the expression of cytochromes P450 and efflux transporters in Haemonchus contortus female and male adults - Kellerová, Pavlína; Matoušková, Petra; Lamka, Jiří; Vokřál, Ivan; Szotáková, Barbora; Zajíčková, Markéta; Pasák, Michael; Skálová, Lenka (Veterinary parasitology, 2019)
Haemonchus contortus, one of the most pathogenic of all small ruminant parasites, have developed resistance to all used anthelmintics. Detoxification enzymes, e.g. cytochromes P450 (CYPs) and efflux transporters P-glycoproteins (P-gps), which represent the main defense system against harmful xenobiotics, have been suggested to contribute to drug resistance development. The present study was designed to compare the constitutive expression of individual CYPs and P-gps in females and males of H. contortus adults and to follow up on the changes in expression of these genes in nematodes exposed to sub-lethal concentrations of ivermectin (IVM), which might occur during inaccurate treatment. The adults of inbred susceptible-Edinburgh strain (ISE, MHco3) of H. contortus were used for this purpose. The nematodes were incubated ex vivo with or without IVM (1, 10 and 100 nM) in culture medium for 4, 12 and 24 h. After incubation, total RNA was isolated and expression levels of individual CYPs and P-gps were analyzed using qPCR. Our results showed a great variability in the constitutive expression of individual CYPs and P-gps in H. contortus adults. The constitutive expression as well as the inducibility of CYPs and P-gps significantly differed in males and females. Contact of adult nematodes with sub-lethal IVM concentrations led to only minor changes in expression of CYPs, while expression of several P-gps, particularly pgp-9.2 in males and pgp-10, pgp-11 in females was increased significantly in IVM-exposed nematodes. In conclusion, inaccurate treatment of sheep with IVM might contribute to drug resistance development via increased expression of efflux transporters in H. contortus adults.
Keywords: Haemonchus; Animals; léková rezistence; P-glykoproteiny; ivermektin; regulace genové exprese; Drug Resistance; Female; Gene Expression Regulation; zvířata; mužské pohlaví; ATP Binding Cassette Transporter, Subfamily B; Male; Cytochrome P-450 Enzyme System; systém (enzymů) cytochromů P-450; ženské pohlaví; Ivermectin